2001
DOI: 10.1007/3-540-44512-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Theories of Langmuir Circulation: A Story of Mixing

Abstract: Abstract. The study of Langmuir circulation has a strongly interdisciplinary history; the first half of this work is a brief and eclectic review of this. Much of the research has been motivated by interest in the biology and chemistry of the mixed layer. These, in turn, are sensitive to details of typical particle trajectories; i.e., to high-order statistics of the flow such as time and space lagged covariances. In contrast, descriptions of the mixed layer have progressed from means (mixed layer velocity, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…As another example, we examine in § 5.3 the case of a waves scattered by sinusoidal current in constant depth, and show that there are cases where strong enhancement of the wave amplitude could be obtained within downwave-directed current jets. This is in agreement with previous observations which suggested that wind-wave amplitudes might be enhanced within the downwind-directed current maxima associated with alternating 'wind streaks' or 'Langmuir circulation' (Smith 1983(Smith , 2001, leading to preferential breaking of waves along such current jets. Finally, in § 5.4, we investigate the influence of longshore-type currents over sinusoidal bottom topography on the Bragg scattering of obliquely incident water waves and discuss their effects on the shifting of the first-order resonant frequencies and the enhancement/reduction of reflection.…”
Section: Introductionsupporting
confidence: 93%
“…As another example, we examine in § 5.3 the case of a waves scattered by sinusoidal current in constant depth, and show that there are cases where strong enhancement of the wave amplitude could be obtained within downwave-directed current jets. This is in agreement with previous observations which suggested that wind-wave amplitudes might be enhanced within the downwind-directed current maxima associated with alternating 'wind streaks' or 'Langmuir circulation' (Smith 1983(Smith , 2001, leading to preferential breaking of waves along such current jets. Finally, in § 5.4, we investigate the influence of longshore-type currents over sinusoidal bottom topography on the Bragg scattering of obliquely incident water waves and discuss their effects on the shifting of the first-order resonant frequencies and the enhancement/reduction of reflection.…”
Section: Introductionsupporting
confidence: 93%
“…This criticism is mostly directed at the failure of experimentalists to obtain sufficiently systematic and quantitative data sets necessary for such validation. The measurements of LT that are available in the literature tend to be either indirect or episodic and insufficiently quantitative (e.g., Gargett & Wells, ; Melville et al, ; Smith, ; Weller et al, , among others), thus lacking the systematic quality necessary for conclusive model evaluation. This, in part, motivates the present study and sets an objective to provide a benchmark data set that can be used for validation of wave‐driven aspects of LES.…”
Section: Introductionmentioning
confidence: 99%
“…It is the interaction of Stokes drift with wind-driven surface shear flow that induces Langmuir circulation (LC) formation [2]. As one of the most significant features of the mixed layer, LC appears as an array of alternating horizontal roll vortices, whose axes are roughly parallel to the wind direction [3][4][5]. LC could enhance the vertical mixing and alter vertical profiles of temperature and velocity [6][7][8][9], making it crucial in upper ocean studies.…”
Section: Introductionmentioning
confidence: 99%